Cyclodextrins: A promising drug delivery vehicle for bisphosphonate. (20th January 2017) - Monteil, Maelle; Lecouvey, Marc; Landy, David; Ruellan, Steven; Mallard, Isabelle
Highlights: Successfull cyclodextrin/bisphosphonates complex formation. Cyclodextrins carriers for bisphosphates. New systems for drug formulation. Abstract: Bisphosphonates are well established pharmaceutical drugs with wide applications in medicine. Nevertheless, the side chain and the nature of phosphorous groups could induce a poor aqueous solubility and act on their bioavailability. At the same time, cyclodextrins are cage molecules that facilitate transport of hydrophobic molecules to enhance the intestinal drug absorption of these molecules by forming inclusion complexes. Here we demonstrate that cyclodextrins could be used as a bisphosphonate carrier. The formation of cyclodextrins-bisphosphonate complexes was characterized by 1D and 2D NMR spectroscopy, Isothermal Titration Calorimetry and UV–vis spectroscopy. The results revealed that only the side chain of bisphosphonate was involved in the inclusion phenomenon and its length was a crucial parameter in the control of affinity. Findings from this study suggest that cyclodextrin will be a useful carrier for bisphosphonates.